Prediksi financial distress dengan analisis risk, good corporate governance, earningsc Capital, dan size pada Bank Umum Swasta Nasional Devisa - Elysa Lisitiana Putri (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2018)
The research aims to predict financial distress at the Foreign Exchange National Private Commercial Bank by using analysis of risk, good corporate governance, earnings, capital and size. Using sample 17 national foreign exchange private banks, and data analysis techniques using Multiple Linear Regression for four conditions, namely all conditions, financial distress conditions, gray area conditions, and non financial distress conditions. The results of this study indicate that the NPL and the proportion of independent commissioners do not have a significant effect on all conditions, financial distress conditions, gray area conditions, and non financial distress conditions. ROA has a significant effect only for all conditions, gray area, and non financial distress conditions. CAR has a significant effect on all conditions, and financial distress conditions, size only has a significant effect on all conditions and conditions in the gray area.